Development of Automatic Litter Box Using ESP32 - Zainal, Muhammad Hazwan; Chua King Lee (Evolution in Electrical and Electronic Engineering, 2023)
The necessity to filter the clumping litter itself is a filthy activity that can generate an unpleasant odour if left neglected in litter boxes. In response to the preceding remark, Smart Litter Box is a work that will aid pet owners in resolving the most common problem encountered while cleaning their pet. In this study, a litter box is created that can autonomously clean cat faeces and refill the sand dispenser. Passive Infrared Motion Sensor is used to detect cat movement when it is inside the litter box and also cat faeces. A servo motor is employed to release sand from the dispenser, controlled through the Blynk application. Stepper motor used to move the filter in forward and opposite direction to be able push cat faeces. The Automatic Litter Box achieved its intended success, smoothly completing the cleaning process in a modest 4 minutes to make cat poop itself inside litter box and then the filter will scoop the faeces until it falls to storage area. It also has an alerting system notification which notify through the phone by email application make pet owner ready to remove the faeces any time by connecting Wi-Fi. A noticeable relationship became evident between the quantity of cat faeces present in the litter box and the distance it could travel. As the amount of faeces increased, the litter box's ability to cover distance decreased, highlighting the influence of heavier loads on its mobility.